Back Cover Advanced Engineering Materials 1‐2/2013. Issue 1 (8th February 2013) - Davidson, Marc; Roberts, Scott; Castro, Gerhard; Dillon, Robert Peter; Kunz, Allison; Kozachkov, Henry; Demetriou, Marios D.; Johnson, William L.; Nutt, Steve; Hofmann, Douglas C.
<x xml:space="preserve">Abstract</x> Long‐exposure image of a hypervelocity impact between an aluminum projectile traveling at 3 km/s and a three‐layer bulk metallic glass composite foam. Owing to their unique combination of high hardness, low density, and low melting temperatures, metallic glasses appear to be optimal materials for orbital debris shields for spacecraft and satellites in low‐earth‐orbit. In this article, Davidson et. al. perform the first evaluation of these non‐crystalline materials under hypervelocity impacts. Further details can be found by D. C. Hofmann et al. on page 27. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>